Pathological confirmation of nerve‐sparing types performed during robot‐assisted radical prostatectomy (RARP). (20th August 2012) - Ko, Woo Jin; Hruby, Gregory W.; Turk, Andrew T.; Landman, Jaime; Badani, Ketan K.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Incremental nerve‐sparing techniques (NSTs) improve postoperative erectile function after robot‐assisted radical prostatectomy (RARP). However, there are no studies to date that histologically confirm the surgeon intended NST. Thus, in the present study, we histologically confirmed that the surgeon performed the nerve preservation as his intended NSTs during RARP. Also, we found that there was more variability in fascia width outcome on the left side compared with the right. Therefore, when performing nerve preservation on the surgeon's non‐dominant side, we need to pay more close attention. Objectives To confirm that the surgeon achieved true intended histological nerve sparing during robot‐assisted radical prostatectomy (RARP) by studying RP specimens. To aid the novice robotic surgeon to develop the skills of RARP. Patients and Methods Between June 2008 and May 2009, 122 consecutive patients underwent RARP by a single surgeon (K.K.B.). The degree of nerve sparing (wide resection [WR], interfascial nerve sparing [ITE‐NS], intrafascial nerve sparing [ITR‐NS]) on both sides was recorded. The posterior sectors of RP specimens from distal, mid, and proximal parts were evaluated. Fascia width (FW) of each position in RP specimens were compared across nerve‐sparing types (NSTs). FW was recorded at 15 ° intervals (3–9 o'clock position), measured as the distance between the outermost prostate gland and surgical margin. The slides were reviewed by an experienced uropathologist who was 'blinded' to the NST. Results In all, 93 men were included. The overall mean (sd) FW was the greatest in the order of WR, ITE‐NS, and ITR‐NS, at 2.42 (1.62), 1.71 (1.40) and 1.16 (1.08) mm, respectively (P < 0.001). FW was statistically significantly correlated with the surgical technique used. When the surgeon intended to perform various levels of nerve sparing, these were reflected in the FW. Interestingly, the left‐side FW showed more variability than the right side. We suspect that this was a result of the surgeon's right‐hand dominance. Erectile function (EF) recovery rate according to NST was 88.9%, 77.3%, 65.6%, 56.3%, and 0% in bilateral ITR‐NS, ITR‐NS/ITE‐NS, bilateral ITE‐NS, ITE‐NS/WR, and bilateral WR, respectively. To further validate and confirm these preliminary findings, additional studies involving multicentre cohorts would be required. Conclusions The surgeon intended dissection and FW correlate, with ITR‐NS providing the narrowest FW and the EF recovery rate was the highest in bilateral ITR‐NS. There was more variability in FW outcome on the left side than the right. The novice robotic surgeon should consider this variability when performing RARP. It may have implications for technique improvement on nerve preservation for EF.